Statistical Data About Risk Factors and Pregnancy Outcome of Placenta Previa - Arian, Kashami; Amela, Troshani; Zamira, Shabani (European Scientific Journal, ESJ, 2018)
Placenta previa is a placental location close to or over the internal cervical os. The aim of this study was to evaluate: risk factors, maternal and neonatal outcomes in patients with placenta previa. Material and methods: We conducted a retrospective cohort study of 38 women who have had a caesarean section for placenta previa at a tertiary referral University Hospital of Obstetrics and Gynecology “Koço Gliozheni” in Tirana, Albania. The period of this study was from January 2015 to March 2018. Maternal and neonatal data were obtained from medical records and the hospital database system. All cases of placenta previa were managed by medical team, obstetric consultants and all data were calculated with SPSS.20 program. Results: In total, 38 women with placenta previa were classified in three different types of placenta previa: Marginal placenta previa occurred in 16 women(42.1%), Complete placenta previa occurred in 19 women(50%) and with accreta placenta previa in 3 women(7.9%). The mean age of mothers was 30,61 years old, mode = 35, median = 30 and Std. deviation = 4.641 years. Conclusions: The prevalence rate of section caesarean and placenta previa is increased during the years. Several obstetrical factors have been found to be risk for placenta previa including: advancing maternal age, previous caesarean delivery, previous abortions, previous uterine surgery, multiparity, previous placenta previa, low socio-economic status, mother’s cigarette smoking /alcohol use. Placenta previa is associated with an increase in preterm birth and neonatal and maternal outcome. Other complications of pregnancy can be associated with placenta previa, but the majority of women deliver healthy babies.